1995
DOI: 10.1207/s15327019eb0501_6
|View full text |Cite
|
Sign up to set email alerts
|

Deceived Versus Nondeceived Participants' Perceptions of Scientific and Applied Psychology

Abstract: Research examining the possible effects of deceptive research participation on participants' perceptions of psychology has yielded equivocal results. The present study's goal was to clarify the possible effects of participation in mildly deceptive research on participants' impressions of scientific and applied psychology. Participants (N = 112) were randomly assigned to one of six experimental conditions: active groups receiving negative, positive, or no feedback, or passive groups receiving negative, positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although Kelman (1967) assumed that the constant use of deception would cause research participants to become distrustful; Sharpe et al (1992) found that the participants accepted the arguments justifying the use of deception; Soliday and Stanton (1995) found that mild deception had no effect on the participants' attitudes toward researchers; Fisher and Fyrberg (1994) found that most of the student participants believed that the deception made studies scientifically valid and valuable, hence, its use was methodologically important, even when alternative ways, such as role playing or questionnaires, were also available. Despite these findings, in real life, the use of deceptions may not be regarded such valuable or important.…”
Section: (2) Trustmentioning
confidence: 99%
“…Although Kelman (1967) assumed that the constant use of deception would cause research participants to become distrustful; Sharpe et al (1992) found that the participants accepted the arguments justifying the use of deception; Soliday and Stanton (1995) found that mild deception had no effect on the participants' attitudes toward researchers; Fisher and Fyrberg (1994) found that most of the student participants believed that the deception made studies scientifically valid and valuable, hence, its use was methodologically important, even when alternative ways, such as role playing or questionnaires, were also available. Despite these findings, in real life, the use of deceptions may not be regarded such valuable or important.…”
Section: (2) Trustmentioning
confidence: 99%
“…A number of studies have found that deception does not upset most subjects. [8][9][10][11] Soliday and Stanton 9 found that subjects were not bothered by the use of deception in 6 experimental scenarios. Indeed, Smith and Richardson 10 report that subjects who had been deceived in psychology experiments rated their overall experience as more positive than those who had not been deceived.…”
Section: The Harms Of Deceptionmentioning
confidence: 99%